Supporting women after domestic violence : loss, trauma and recovery - Abrahams, Hilary, 1941- (Jessica Kingsley Publishers, 2007)
Drawing on the direct experiences of women who have encountered domestic violence, this book sets out to explore the complex practical and emotional support they need. It will be a key resource for those working within women's refuges, as well as social workers, counsellors, psychotherapists and mental health professionals.